P2-S2.07 Improving sexually transmitted infections (STI) prevention strategies: factors associated with STIs among female sex workers in India. (10th July 2011) - Narayanan, P; Das, A; Gurung, A; Parimi, P; Rao, G; Risbud, A
Abstract : Background: Studies among high-risk groups (HRGs) have shown that the presence of STIs is associated with certain demographic and behavioural characteristics as well as exposure to HIV/STI prevention interventions. The objective of this study was to understand the correlates of STIs in female sex workers (FSWs) in India in order to improve STI programming for HRGs. Methods: During 2008–2009, 417 female sex workers were recruited from three STI clinics in two cities of India as part of an operations research to evaluate the effectiveness of STI prevention service package for sex workers under Avahan, the India AIDS Initiative of the Bill & Melinda Gates Foundation. Behavioural and clinical information along with biological samples were collected. Bivariate analysis of demographic and behavioural characteristics associated with the prevalence of common bacterial STIs- Neisseria gonorrhoeae, Chlamydia trachomatis, Treponema pallidum and Trichomonas vaginalis from the baseline data is presented in this paper. Results: At baseline 49.2% of the participants had a laboratory confirmed diagnosis for at least one of the four bacterial STIs. The significant factors associated with STI prevalence among FSWs were: inability to read or write (OR=2.2, p=0.002); not staying with a sexual partner (OR=1.5, p=0.036); typology of sex work: home-/hotel-based (OR=2.5, p=0.038) vs brothel-based and street-based (OR=3.1, p=0.004) vs brothel-based; regular or occasional consumption of alcohol (OR=1.9, p=0.002); poor knowledge of STI symptoms (OR=1.6, p=0.017); low self-risk perception for acquiring STIs (OR=1.6, p=0.031); less than 2 years in sex work (OR=1.8, p=0.008); no prior exposure to HIV/STI interventions (OR=2.0, p=0.001); and no STI check-ups in the past 6 months (OR=1.5, p=0.029) see Abstract P2-S2.07 Table 1 . Conclusions: HIV/STI prevention programs for FSWs in India need to prioritise services for HRGs who have characteristics associated with STI prevalence. Additionally, awareness activities should promote the importance of regular STI check-ups, recognition and early treatment for STI symptoms.